Design of Employment Administration Information System at PT Kopaba Jatim on Web-Based - Septarian, Alif Zakariya; Nurcahyawati, Vivine; Churniawan, Agus Dwi (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
PT Kopaba Jatim is a business entity engaged in manpower distribution to the Bank Jatim’s branches. PT Kopaba Jatim joint moves with Bank Jatim cooperative. Manpower provided by these companies is security, drivers and office boy. PT Jatim Kopaba have a problems associated with data employee. Some problems are piled up files, employee history data less accurate, and the difficulty in performing insert, update, delete. Moreover, in the process of making contracts letter, mutation letter and termination letter took a long time because the system is based on Microsoft Excel that can be accessed by one client only, Microsoft Excel are also less effective to monitor the employees in nearly all branches of Bank Jatim. Based on the issues, PT Kopaba should have a system to facilitate the process of personnel administration. So the correct solution is the making of personnel administration information system that can determine which employees will be out of contract next three months, facilitate administrative processes and simplify the employee making the report related. With this system, employee data collection process becomes more effective. Report generation is more accurate. Also based on alpha test with 27 function test result is 100% according to user needs.